The Effect of Using The Snowball Drilling Learning Model In Learning Islamic Religious Education (PAI) Class XI MA DDI Mattoanging Students - Nurfahmi Afrian (Pelopor Publikasi Akademika, 2024)
This research aims to determine the effect of using the Islamic Religious Education learning model for class XI students at MA DDI Mattoanging. This research is a type of classroom action research, with the Snowball Throwing learning method. The research subjects were 20 class XI students at MA DDI Mattoanging and what was observed was student activity and student learning outcomes. The data collection technique in this research uses observation and documentation sheets. Based on the research results, it has provided concrete evidence regarding the use of the Snowball Drilling learning model in the learning process. Therefore, this model can help teachers to make it easier for students to easily understand Islamic Religious Education learning. This was obtained from the results of direct interviews conducted with class XI MA DDI Mattoanging students. After the researchers analyzed several research results, the researcher concluded that Islamic Religious Education learning is a teaching and learning process carried out by teachers to achieve a learning goal